Bioactive compounds and antioxidant activity of different extracts from Vitex negundo leaf - Zargar, Mohsen; Abdul Hamid, Azizah; Mustafa, Roheeyati Ashikin; Abu Bakar, Fatimah; Jahanshiri, Fatemeh; Pak Dek, Mohd Sabri (Academic Journals, 2011)
The study was conducted to assess the antioxidant activity of methanol and hexane extract and essential oil from Vitex negundo leaf using different in vitro antioxidant assays. Antioxidant property was tested using 2,2-diphenyl-1-picrylhydrozyl (DPPH) free radical scavenging capacity, ferric ion reducing antioxidant power (FRAP) and β-carotene-linoleic acid assays. Total phenolic contents (TPC) were measured using Folin-Ciocalteu method. Flavonoids, tocopherols, β-carotene and lycopene were analyzed using high performance liquid chromatography (HPLC). Results of the present study showed that methanol extract of V. negundo leaf exhibited significantly (p < 0.05) higher antioxidant activity in terms of measurements of DPPH free radical (IC50), FRAP and β-carotene-linoleic assays than those of hexane extract and essential oil. Methanol extract of V. negundo leaf also contained high amounts of bioactive compounds including total phenolic compounds (363 mg GAE/g), epicatechin (16.98 mg/g), quercetin (13.45 mg/g), catechin (8.95 mg/g) and myricetin (3.32 mg/g) while the concentrations of tocopherol, β-carotene and lycopene were found to be lower.